MINERALOGY OF PGE IN THE MAFIC-ULTRAMAFIC MASSIFS OF THE KOLA REGION - Yakovlev Yu.N.; Mitrofanov F.P.; Razhev S.A.; Veselovsky N.N.; Distler V.V.; Grokhovskaya T.L. (My University, 1991)
During the last few years nearly 50 minerals and unnamed platinum-group element (PGE) phases have been identified by the authors in nickel-bearing mafic-ultramafic massifs of the Kola region. About 20 established PGE minerals have been found whilst more than 20 previously undescribed and unnamed PGE phases can be reported. In addition high concentrations of these elements in sulfarsenides of the cobaltitegersdorffite series have been established. The PGE phases form tiny (5-70 μm, seldom larger) mono- and polymineral inclusions in the main sulfides of the nickel-copper mineralization; at the contacts with silicates and within the silicates themselves. The details of the composition of platinum mineralization in various massifs, its formation under magmatic and hydrothermal conditions and wide isomorphism in certain groups of minerals have been established. Specific features of PGE mineralization of the region as a whole are: the predominance of bismuth tellurides and arsenides of palladium and platinum, a highly subordinated role of their sulphides and higher concentrations of several PGE in sulfarsenides.